The Chinese National Twin Registry: a 'gold mine' for scientific research. (4th July 2019) - Gao, W.; Cao, W.; Lv, J.; Yu, C.; Wu, T.; Wang, S.; Meng, L.; Wang, D.; Wang, Z.; Pang, Z.; Yu, M.; Wang, H.; et al.
Abstract: The Chinese National Twin Registry (CNTR) currently includes data from 61 566 twin pair from 11 provinces or cities in China. Of these, 31 705, 15 060 and 13 531 pairs are monozygotic, same‐sex dizygotic and opposite‐sex dizygotic pairs, respectively, determined by opposite sex or intrapair similarity. Since its establishment in 2001, the CNTR has provided an important resource for analysing genetic and environmental influences on chronic diseases especially cardiovascular diseases. Recently, the CNTR has focused on collecting biologic specimens from disease‐concordant or disease‐discordant twin pairs or from twin pairs reared apart. More than 8000 pairs of these twins have been registered, and blood samples have been collected from more than 1500 pairs. In this review, we summarize the main findings from univariate and multivariate genetic effects analyses, gene–environment interaction studies, omics studies exploring DNA methylation and metabolomic markers associated with phenotypes. There remains further scope for CNTR research and data mining. The plan for future development of the CNTR is described. The CNTR welcomes worldwide collaboration. Abstract :